Addressing complex challenges using a co-innovation approach: Lessons from five case studies in the New Zealand primary sector. (June 2017) - Vereijssen, Jessica; Srinivasan, MS; Dirks, Sarah; Fielke, Simon; Jongmans, Catharina; Agnew, Natasha; Klerkx, Laurens; Pinxterhuis, Ina; Moore, John; Edwards, Paul; Brazendale, Rob; Botha, Neels; et al.
Co-innovation can be effective for complex challenges – involving interactions amongst multiple stakeholders, viewpoints, perceptions, practices and interests across programmes, sectors and national systems. Approaches to challenges in the primary sector have tended to be linear, where tools and outputs are developed by a few, mostly scientists/researchers, and then extended to stakeholders. A co-innovation approach first deciphers and delineates the biophysical, societal, regulatory, policy, economic and environmental drivers, constraints and controls influencing these challenges at multiple levels. Second, stakeholder interactions and perspectives can inform and change the focus as well as help in co-developing solutions to deliver agreed outcomes. However, there is limited systematic and comparative research on how co-innovation works out in different projects. Here we analyse the results of applying a co-innovation approach to five research projects in the New Zealand primary sector. The projects varied in depth and breadth of stakeholder engagement, availability of ready-made solutions and prevalence of interests and conflicts. The projects show how and why co-innovation approaches in some cases contributed to a shared understanding of complex problems. Our results confirm the context specificity of co-innovation practices.